Risk analysis and mitigation strategies for preventing corrosion during industrial power failure - Li, Jia Yang (Nanyang Technological University, 2021)
Modern civilisation depends on many different sectors functioning well and concurrently to run smoothly. This includes the energy sector, the transport sector, and the information technology sector, to name a few. As such, the consequences can be catastrophic if these sectors were to fail and remain out of commission for 1 to 25 years, due to some form of power outage or disaster. Possible causes include a high-altitude electromagnetic pulse from a nuclear bomb or a solar storm, a pandemic worse than COVID-19 causing people to be too fearful to work in critical industries, a cyber-attack, or an extreme natural disaster. Some work has been done on what could happen if such sectors are disabled, but virtually none on how to cope or to prepare for the loss. First, estimates of how long such a power outage will last was calculated. Next, scenarios where there is a power loss in industry for at least 5 to 25 years was explored. The consequences of such a scenario with regards to corrosion was considered. Possible strategies for what can be done to prepare for such scenarios were also explored. It was found that considering the design, removing corrosive components, and using coatings and packaging were the cheapest ways to reduce corrosion risks.